Preparation method of liquid-phase oxidized starch-based hard carbon material, hard carbon material and application of hard carbon material
The preparation of hard carbon materials by liquid phase oxidation method solves the problems of uneven preoxidation effects and environmental pollution in traditional methods, and achieves hard carbon materials with high compaction density, low resistivity and excellent sodium storage performance.
Patent Information
- Application Number
- CN202411789600.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-02-28
AI Technical Summary
The preparation method of traditional hard carbon negative electrode materials has problems such as uneven preoxidation effects, equipment corrosion and environmental pollution, and it is difficult to effectively regulate the growth of carbon microcrystals and the capture ability of sodium ions.
The hard carbon material is prepared by liquid phase oxidation method. By reacting starch, oxidant and solvent medium in a sealed reactor, the reaction product is washed, dried and carbonized by water to obtain a hard carbon material with high compaction density and low resistivity.
The high compaction density and low resistivity of hard carbon materials are achieved, which significantly improves the sodium storage performance and Coulomb efficiency of the material, and reduces the pressure of equipment corrosion and environmental pollution.
Smart Images

Figure CN119528117A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a hard carbon material, also relates to a method for preparing the hard carbon material by a liquid phase oxidation method, and also relates to the application of the hard carbon material, belonging to the technical field of battery materials. Background Art
[0002] In the preparation process of hard carbon negative electrode materials, pre-oxidation of carbon material precursors is a core link, especially for hydrogen-rich precursor materials. Pre-oxidation can effectively regulate the growth of carbon crystallites during carbonization. In addition, the special oxygen-containing functional groups introduced into the carbon skeleton during the pre-oxidation process have a positive effect on enhancing the material's ability to capture sodium ions. However, traditional pre-oxidation methods, such as air (or pure oxygen) solid-phase oxidation and mixed acid (nitric acid + sulfuric acid) liquid-phase oxidation, have significant defects. For example, the solid-phase oxidation method may result in uneven or insufficient pre-oxidation effects due to insufficient contact between the gas phase and the solid phase; for example, the mixed acid liquid-phase oxidation method causes greater corrosion to the equipment and is accompanied by serious environmental pollution problems. Summary of the invention
[0003] In view of the defects of the prior art, the first object of the present invention is to provide a hard carbon material having a high compaction density (up to 1.025 g / cm 3 Above), and under a pressure of 100MPa, it exhibits extremely low resistivity.
[0004] The second object of the present invention is to provide a method for preparing hard carbon materials. The method prepares a hard carbon material precursor by a liquid phase oxidation method, which not only overcomes the problem of insufficient gas-solid phase contact, but also significantly reduces the corrosiveness and environmental pollution pressure of the mixed acid on the equipment, showing the significant advantages of green environmental protection and high cost-effectiveness.
[0005] The third object of the present invention is to provide an application of a hard carbon material, which is used in an alkali metal secondary battery and exhibits excellent sodium storage performance with a first-cycle coulombic efficiency of 90%.
[0006] In order to achieve the above technical objectives, the present invention provides a method for preparing a liquid-phase oxidized starch-based hard carbon material, which comprises reacting starch, an oxidant and a solvent medium in a sealed reactor at a temperature of 25 to 90°C, and the reaction product is sequentially washed, dried and carbonized to obtain a hard carbon material; the oxidant comprises at least one of an ammonium persulfate-acid system, hydrogen peroxide, and a sodium hypochlorite-acid system.
[0007] The present invention realizes oxidation of starch through liquid phase oxidation method, utilizes the strong oxidizing property of oxidants such as ammonium persulfate-acid system, hydrogen peroxide, sodium hypochlorite-acid system, and realizes in-depth and uniform oxidation treatment of starch under appropriate temperature and pressure conditions. After the oxidation treatment, the starch introduces rich oxygen-containing functional groups into its carbon skeleton, which can not only suppress the volume expansion problem during the high-temperature carbonization process, but also effectively regulate the growth of carbon microcrystals, thereby facilitating the improvement of the sodium storage performance of the hard carbon material.
[0008] Since the liquid phase oxidation method adopts a hydrothermal process, the biggest problem in the hydrothermal process is that starch is easily hydrothermally carbonized. Therefore, in order to ensure that the starch is fully oxidized while avoiding hydrothermal carbonization of the starch, it is necessary to select a suitable oxidation system and control appropriate reaction conditions.
[0009] As a preferred solution, the mass concentration of the starch in the solvent medium is 1 to 45%. Too low a mass concentration of starch will indirectly increase the preparation cost of the hard carbon material, and too high a concentration of starch will affect its dispersibility in the solvent medium. The mass concentration of the starch in the solvent medium is further preferably 30 to 40%.
[0010] As a more preferred solution, the starch includes at least one of corn starch, wheat starch, potato starch and rice starch. Based on the differences in the microscopic results of various starches, a large number of experiments have shown that corn starch is more conducive to obtaining hard carbon materials with good sodium storage performance than other starches.
[0011] As a preferred solution, when the oxidant is hydrogen peroxide, the mass concentration of H2O2 in the solvent medium is 5% to 20% (a further preferred mass concentration is 8% to 15%); when the oxidant is an ammonium persulfate-acid system or a sodium hypochlorite-acid system, the mass concentration of ammonium persulfate or sodium hypochlorite in the solvent medium is 5% to 20% (a further preferred mass concentration is 8% to 15%), and the concentration of the acid in the solvent medium does not exceed 3M. If the amount of the oxidant is excessive, the starch will be over-oxidized, resulting in a hard carbon material generated by high-temperature carbonization having a higher specific surface area and porosity, which will reduce the sodium storage capacity of the hard carbon material. If the amount of the oxidant is too low, the expected oxidation effect will not be achieved. The ammonium persulfate-acid system is the most preferred oxidant. The oxidation ability of ammonium persulfate is significantly improved under the action of acid, which is particularly suitable for the oxidation modification process of starch. The concentration of the acid in the solvent medium is further preferably 0.05 to 2M. A solution with too high an acid concentration will cause starch hydrolysis. Under appropriate acidic conditions, the oxidizability of ammonium persulfate can be significantly improved, thereby increasing the oxidizing effect on starch. The solvent medium is, for example, water. Starch is generally hydrophilic and can be easily dispersed evenly in water.
[0012] As a preferred embodiment, the acid comprises at least one of formic acid, acetic acid, oxalic acid, malic acid, citric acid, hydrochloric acid, sulfuric acid and hypochlorous acid. The most preferred acid is acetic acid.
[0013] As a preferred solution, the reaction temperature is 40 to 80°C and the reaction time is 6 to 24 hours. The reaction temperature is further preferably 50 to 70°C and the reaction time is further preferably 10 to 16 hours. Under appropriate temperature conditions, the oxidation activity can be increased, the process of the oxidation reaction can be accelerated, and the uniformity of the oxidation can be improved. If the temperature is too high, hydrothermal carbonization will occur, affecting the subsequent yield and electrochemical properties of the hard carbon material. The solvent medium is such as water.
[0014] As a preferred solution, the carbonization conditions are: temperature of 1000-1700°C, time of 1-12 hours, and the carbonization temperature is more preferably 1200-1500°C.
[0015] The present invention also provides a hard carbon material obtained by the preparation method. After the starch is pre-oxidized in the liquid phase and carbonized at high temperature, the original morphology of the starch is basically maintained. The compaction density of the obtained hard carbon material can reach 1.025g / cm 3 Above, and under a pressure of 100MPa, it exhibits extremely low resistivity.
[0016] The present invention also provides an application of the hard carbon material as a negative electrode material for an alkali metal secondary battery. Alkali metals such as sodium exhibit high sodium storage performance, and have a first-cycle coulomb efficiency of 90%.
[0017] Compared with the prior art, the technical solution of the present invention has the following beneficial technical effects:
[0018] The present invention prepares hard carbon precursor materials through liquid phase oxidation method, which not only overcomes the problem of insufficient gas-solid phase contact and can improve the oxidation degree and oxidation uniformity of starch, but also significantly reduces the corrosiveness and environmental pollution pressure of mixed acid on equipment, showing the significant advantages of green environmental protection and high cost-effectiveness.
[0019] In the process of preparing the hard carbon precursor material by the liquid phase oxidation method of the present invention, the carbonization process of starch can be effectively avoided by selecting a suitable oxidation system and controlling the reaction conditions, so that the original morphology of starch can be maintained after pre-oxidation.
[0020] The hard carbon material prepared by the present invention has high compaction density and low resistivity, and when used in sodium ion batteries, it not only exhibits excellent sodium storage performance, but also has a first-cycle coulomb efficiency of 90%. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is the SEM image of the hard carbon material prepared in Example 1.
[0022] Figure 2 This is the SEM image of the hard carbon material prepared in Comparative Example 1.
[0023] Figure 3 This is a curve chart showing how the compaction density of the hard carbon material prepared in Example 1 changes with pressure.
[0024] Figure 4 This is a curve showing how the resistivity of the hard carbon material prepared in Example 1 changes with pressure.
[0025] Figure 5 The voltage distribution curve of the hard carbon materials prepared in Examples 1, 2, 3 and 5 in a sodium ion battery.
[0026] Figure 6 The voltage distribution curve of the hard carbon material prepared in Example 8 and Comparative Example 1 in a sodium ion battery. DETAILED DESCRIPTION
[0027] The present invention is described in detail below with reference to embodiments, but the protection scope of the claims of the present invention is not limited to these embodiments.
[0028] Example 1
[0029] First, prepare a 1M acetic acid solution, and then add 10% ammonium persulfate to fully dissolve it. Weigh an appropriate amount of corn starch at 40% solid content, then transfer it to a sealed reactor and disperse it evenly, and then keep it at 60℃ for 12 hours. After naturally cooling to room temperature, wash it thoroughly and dry it to obtain a hard carbon precursor material. Transfer it to a graphite boat, carbonize it at 1300℃ for 3 hours, and naturally cool it to room temperature to obtain a black powder solid (HC-APS-1). Figure 1 The prepared HC-APS-1 is in a uniform granular form, effectively maintaining the original morphology of starch and having a smooth surface. Compared with Comparative Example 1, the hydrolysis of ammonium persulfate to produce sulfate ions promotes the hydrolysis of starch, resulting in a rough surface of the hard carbon material and a sudden increase in specific surface area ( Figure 2 ).like Figures 3-4 The compacted density of the material further tested using a powder conductivity meter is 1.025 g / cm 3 The above, under a pressure of 100MPa, also showed extremely low resistivity. Metallic sodium was used as the counter electrode to assemble a 2016-type button cell with HC-APS-1 to test its sodium storage capacity. The first cycle reversible capacity of HC-APS-1 is 316mAh / g, and the coulombic efficiency is 90.3%. For details, see Figure 5 .
[0030] Example 2
[0031] First, prepare a 1M hydrochloric acid solution, and then add 10% ammonium persulfate to fully dissolve it. Weigh an appropriate amount of corn starch at 40% solid content and transfer it to a sealed reactor for uniform dispersion. Keep it at 60°C for 12 hours, cool it naturally to room temperature, wash it thoroughly, and dry it to obtain a hard carbon precursor material. Transfer it to a graphite boat and carbonize it at 1300°C for 3 hours, cool it naturally to room temperature, and obtain a black powder solid (HC-APS-2). Use metallic sodium as the counter electrode and HC-APS-2 to assemble a 2016 button battery to test its sodium storage capacity.
[0032] Example 3
[0033] First, prepare a 0.1M sulfuric acid solution, and then add 10% ammonium persulfate to fully dissolve it. Weigh an appropriate amount of corn starch at 40% solid content and transfer it to a sealed reactor for uniform dispersion. Keep it at 60°C for 12 hours, cool it naturally to room temperature, and then wash and dry it thoroughly to obtain a hard carbon precursor material. Comparison shows that sulfuric acid as an acidic environment for ammonium persulfate will lead to a lower precursor yield. It is speculated that this may be because sulfuric acid promotes the hydrolysis of starch in the early stage of oxidation. Moreover, as the reaction proceeds, the concentration of sulfate ions will further increase and promote the hydrolysis of starch. The obtained precursor was transferred to a graphite boat and carbonized at 1300°C for 3 hours and naturally cooled to room temperature to obtain a black powder solid (HC-APS-3). Using metallic sodium as the counter electrode and HC-APS-3 to assemble a 2016 button battery to test its sodium storage capacity.
[0034] Example 4
[0035] First, prepare a 1M acetic acid solution, and then add 10% ammonium persulfate to fully dissolve it. Weigh an appropriate amount of potato starch at a solid content of 40% and transfer it to a sealed reactor for uniform dispersion. Keep it at 60°C for 12 hours, cool it naturally to room temperature, wash it thoroughly, and dry it to obtain a hard carbon precursor material. Transfer it to a graphite boat, carbonize it at 1300°C for 3 hours, and cool it naturally to room temperature to obtain a black powder solid (HC-APS-4). Use metallic sodium as the counter electrode and HC-APS-4 to assemble a 2016 button battery to test its sodium storage capacity.
[0036] Example 5
[0037] First, prepare a 1M acetic acid solution, and then add 10% ammonium persulfate to fully dissolve it. Weigh an appropriate amount of wheat starch at a solid content of 40% and transfer it to a sealed reactor for uniform dispersion. Keep it at 60°C for 12 hours, cool it naturally to room temperature, wash it thoroughly, and dry it to obtain a hard carbon precursor material. Transfer it to a graphite boat, carbonize it at 1300°C for 3 hours, and cool it naturally to room temperature to obtain a black powder solid (HC-APS-5). Use metallic sodium as the counter electrode and HC-APS-5 to assemble a 2016 button battery to test its sodium storage capacity.
[0038] Example 6
[0039] First, prepare a 1M acetic acid solution, and then add 10% ammonium persulfate to fully dissolve it. Weigh an appropriate amount of rice starch at a solid content of 40% and transfer it to a sealed reactor. After uniform dispersion, keep it at 60°C for 12 hours, cool it naturally to room temperature, wash it thoroughly, and dry it to obtain a hard carbon precursor material. Transfer it to a graphite boat, carbonize it at 1300°C for 3 hours, and cool it naturally to room temperature to obtain a black powder solid (HC-APS-6). Use metallic sodium as the counter electrode and HC-APS-6 to assemble a 2016 button battery to test its sodium storage capacity.
[0040] Example 7
[0041] First, prepare a 1M acetic acid solution, and then add 10% ammonium persulfate to fully dissolve it. Weigh an appropriate amount of corn starch at a solid content of 40% and transfer it to a sealed reactor for uniform dispersion. Keep it at 50°C for 12 hours, cool it naturally to room temperature, wash it thoroughly, and dry it to obtain a hard carbon precursor material. Transfer it to a graphite boat, carbonize it at 1300°C for 3 hours, and cool it naturally to room temperature to obtain a black powder solid (HC-APS-7). Use metallic sodium as the counter electrode and HC-APS-7 to assemble a 2016 button battery to test its sodium storage capacity.
[0042] Example 8
[0043] Weigh an appropriate amount of corn starch at 40% solid content in 5% medical hydrogen peroxide and transfer it to a sealed reactor for uniform dispersion. Keep it at 40°C for 12 hours, cool it naturally to room temperature, wash it thoroughly, and dry it to obtain a hard carbon precursor material. Transfer it to a graphite boat, carbonize it at 1300°C for 3 hours, and cool it naturally to room temperature to obtain a black powder solid (HC-H2O2-1). Use metallic sodium as the counter electrode and HC-H2O2-1 to assemble a 2016 button cell to test its sodium storage capacity.
[0044] Example 9
[0045] First, prepare a 1M acetic acid solution, and then add 5% sodium hypochlorite to fully dissolve it. Weigh an appropriate amount of corn starch at a solid content of 40% and transfer it to a sealed reactor for uniform dispersion. Keep it at 70°C for 12 hours, cool it naturally to room temperature, wash it thoroughly, and dry it to obtain a hard carbon precursor material. Transfer it to a graphite boat, carbonize it at 1300°C for 3 hours, and cool it naturally to room temperature to obtain a black powder solid (HC-Na-1). Use metallic sodium as the counter electrode and HC-Na-1 to assemble a 2016 button battery to test its sodium storage capacity.
[0046] Example 10
[0047] First, prepare a 1M acetic acid solution, and then add 5% ammonium persulfate to fully dissolve it. Weigh an appropriate amount of corn starch at a solid content of 40%, then transfer it to a sealed reactor and disperse it evenly, and keep it at 60°C for 12 hours. After naturally cooling to room temperature, wash it thoroughly and dry it to obtain a hard carbon precursor material. Transfer it to a graphite boat, carbonize it at 1300°C for 3 hours, and cool it naturally to room temperature to obtain a black powder solid (HC-APS-8). Use metallic sodium as the counter electrode and HC-APS-8 to assemble a 2016 button battery to test its sodium storage capacity.
[0048] Embodiment 11
[0049] First, prepare a 1M acetic acid solution, and then add 15% ammonium persulfate to fully dissolve it. Weigh an appropriate amount of corn starch at a solid content of 40% and transfer it to a sealed reactor. After the contents are evenly dispersed, keep it at 60°C for 12 hours, cool it naturally to room temperature, wash it thoroughly, and dry it to obtain a hard carbon precursor material. Transfer it to a graphite boat, carbonize it at 1300°C for 3 hours, and cool it naturally to room temperature to obtain a black powder solid (HC-APS-9). Use metallic sodium as the counter electrode and HC-APS-9 to assemble a 2016 button battery to test its sodium storage capacity.
[0050] Example 12
[0051] First, prepare a 1M acetic acid solution, and then add 10% ammonium persulfate to fully dissolve it. Weigh an appropriate amount of corn starch at 30% solid content and transfer it to a sealed reactor. After the contents are evenly dispersed, keep it at 60°C for 12 hours, cool it naturally to room temperature, wash it thoroughly, and dry it to obtain a hard carbon precursor material. Transfer it to a graphite boat, carbonize it at 1300°C for 3 hours, and cool it naturally to room temperature to obtain a black powder solid (HC-APS-10). Use metallic sodium as the counter electrode and HC-APS-10 to assemble a 2016 button battery to test its sodium storage capacity.
[0052] Example 13
[0053] First, prepare a 1M acetic acid solution, and then add 10% ammonium persulfate to fully dissolve it. Weigh an appropriate amount of corn starch at a solid content of 40%, then transfer it to a sealed reactor and disperse it evenly. After stirring at room temperature (25°C) for 12 hours, wash it thoroughly and dry it to obtain a hard carbon precursor material. Transfer it to a graphite boat, carbonize it at 1300°C for 3 hours, and cool it naturally to room temperature to obtain a black powder solid (HC-APS-D2). Use metallic sodium as the counter electrode and HC-APS-D2 to assemble a 2016 button battery to test its sodium storage capacity.
[0054] Comparative Example 1
[0055] First, prepare a 10% ammonium persulfate solution, weigh an appropriate amount of corn starch at a solid content of 40%, and then transfer it to a sealed reactor and disperse it evenly. Keep it at 60°C for 12 hours, cool it naturally to room temperature, wash it thoroughly, and dry it to obtain a hard carbon precursor material. Transfer it to a graphite boat, carbonize it at 1300°C for 3 hours, and cool it naturally to room temperature to obtain a black powder solid (HC-APS-D1). The results showed that the yield of HC-APS-D1 was extremely low. It is speculated that this may be because the hydrolysis of ammonium persulfate to produce sulfate ions promotes the hydrolysis of starch. Figure 6 It can be found that the irreversible capacity of HC-APS-D1 in the high-pressure region increases sharply due to its rough surface and large specific surface area. Therefore, ammonium persulfate needs an acidic environment to exert its oxidation effect.
[0056] Comparative Example 2
[0057] First, prepare a 1M acetic acid solution, and then add 10% ammonium persulfate to fully dissolve it. Weigh an appropriate amount of corn starch at a solid content of 40%, then transfer it to a sealed reactor and disperse it evenly, and keep it at 120℃ for 12h. After naturally cooling to room temperature, wash it thoroughly and dry it to obtain a hard carbon precursor material. Transfer it to a graphite boat, carbonize it at 1300℃ for 3h, and cool it naturally to room temperature to obtain a black powder solid. Use metallic sodium as the counter electrode to assemble a 2016 button battery to test its sodium storage capacity.
[0058] Battery test conditions: 1. Voltage window 0-2.5V; 2. Nominal capacity 530mAh / g. Test results are shown in Table 1:
[0059] Table 1 Test data statistics
[0060]
[0061]
[0062] From the analysis of Table 1, we know that:
[0063] As can be seen from Examples 1, 2, and 3, both acetic acid and hydrochloric acid can create a suitable acidic environment for ammonium persulfate (NH4)2S2O8+2H2O→2NH4HSO4+H2O2, but sulfuric acid promotes the hydrolysis of starch. Therefore, the electrochemical performance of the material prepared by using sulfuric acid as an initiator is slightly reduced, and the yield is reduced. Compared with hydrochloric acid, acetic acid is preferred in the present invention because hydrochloric acid promotes the hydrolysis of NH4HSO4 to generate H2SO4, which promotes starch hydrolysis and increases the pressure of equipment corrosion and environmental pollution. Acetic acid is weaker than sulfuric acid, so the relative reaction conditions are relatively mild.
[0064] It can be seen from Examples 1, 4, 5, and 6 that various starches can be used to obtain precursor materials through liquid phase oxidation. However, due to the differences in crystallinity, morphology, molecular chain configuration, etc. of the precursors, potato starch, rice starch, and wheat starch are slightly inferior to corn starch in terms of sodium storage.
[0065] It can be seen from Examples 1, 7, 13 and Comparative Example 2 that the temperature of liquid phase oxidation is crucial to the synthesis of hard carbon materials. If the temperature is too high, micro-carbonization will occur, similar to the preparation of carbon beads from glucose, but if the temperature is too low, the material will not be fully oxidized. Therefore, intuitive differences are shown in the electrochemical performance.
[0066] It can be seen from Examples 1, 8 and 9 that by replacing the oxidant system, the hydrogen peroxide and sodium hypochlorite-acid systems also exhibit excellent liquid-phase oxidation capabilities.
[0067] It can be seen from Examples 1, 10, and 11 that Example 10 expands and foams during the carbonization process due to insufficient oxidation capacity, and it is difficult to regulate the growth of carbon microcrystals. However, excessive oxidant will lead to the introduction of a large number of heteroatoms by peroxidation of the precursor, which will lead to a decrease in the coulombic efficiency of the material. Therefore, it is also crucial to choose an appropriate amount of oxidizing groups.
[0068] It can be seen from Example 1 and Comparative Example 1 that ammonium persulfate requires an acidic environment to exert its oxidizing effect, because the hydrolysis of ammonium persulfate to produce sulfate ions promotes the hydrolysis of starch.
[0069] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A method for preparing a liquid-phase oxidized starch-based hard carbon material, characterized in that: Starch, an oxidant and a solvent medium react in a sealed reactor at a temperature of 25-90° C., and the reaction product is sequentially washed, dried and carbonized to obtain a hard carbon material; the oxidant comprises at least one of an ammonium persulfate-acid system, hydrogen peroxide and a sodium hypochlorite-acid system.
2. The method for preparing a liquid-phase oxidized starch-based hard carbon material according to claim 1, characterized in that: The mass concentration of the starch in the solvent medium is 1-45%.
3. The method for preparing a liquid-phase oxidized starch-based hard carbon material according to claim 2, characterized in that: The starch includes at least one of corn starch, wheat starch, potato starch and rice starch.
4. The method for preparing a liquid-phase oxidized starch-based hard carbon material according to claim 1, characterized in that: When the oxidant is hydrogen peroxide, the mass concentration of H2O2 in the solvent medium is 5% to 20%; When the oxidant is an ammonium persulfate-acid system or a sodium hypochlorite-acid system, the mass concentration of ammonium persulfate or sodium hypochlorite in the solvent medium is 5% to 20%, and the concentration of the acid in the solvent medium does not exceed 3M.
5. The method for preparing a liquid-phase oxidized starch-based hard carbon material according to claim 4, characterized in that: The acid includes at least one of formic acid, acetic acid, oxalic acid, malic acid, citric acid, hydrochloric acid, sulfuric acid, and hypochlorous acid.
6. The method for preparing a liquid-phase oxidized starch-based hard carbon material according to any one of claims 1 to 5, characterized in that: The reaction temperature is 40-80° C. and the reaction time is 6-24 hours.
7. The method for preparing a liquid-phase oxidized starch-based hard carbon material according to claim 1, characterized in that: The carbonization conditions are: temperature of 1000-1700° C. and time of 1-12 hours.
8. A hard carbon material, characterized in that: Obtained by the preparation method according to any one of claims 1 to 7.
9. The use of a hard carbon material according to claim 8, characterized in that: Used as negative electrode material in alkali metal secondary batteries.